Timing of maternal vaccination against COVID-19 for effective protection of neonates: cohort study - Nowakowska, Aleksandra; Lee, Seung Mi; Kim, Minjee; Chun, Jungmin; Kim, Sehyun; Kim, Byung Chul; In, Hyun Ju; Lee, Eunji; Lee, Chanyeong; Lee, Hyeondong; Jang, Yuyeon; Cho, Hansam; et al. (Frontiers in Immunology, 2024)
Although the safety and effectiveness of COVID-19 vaccination during pregnancy have been proven, there is still little data explaining neonatal outcomes of maternal pre-pregnancy vaccination. Here, we investigated the impact of vaccination and SARS-CoV-2 infection on maternal-neonate immune response in a cohort study involving 141 pregnant individuals, and defined the importance of maternal COVID-19 vaccination timing for its effectiveness. Our data indicate that vertically transferred maternal hybrid immunity provides significantly better antiviral protection for a neonate than either maternal post-infection or post-vaccination immunity alone. Higher neutralization potency among mothers immunized before pregnancy and their newborns highlights the promising role of pre-pregnancy vaccination in neonatal protection. A comparison of neutralizing antibody titers calculated for each dyad suggests that infection and pre-/during-pregnancy vaccination all support transplacental transfer, providing the offspring with strong passive immunity against SARS-CoV-2. Analysis of neutralizing antibody levels in maternal sera collected during pregnancy and later during delivery shows that immunization may exert a positive effect on maternal protection.